(untitled) (Comprehensive Journal of Science, 2025)
The Role of Positive Heritage in Enhancing Cultural Awareness: A Study in the Works of Ahmed Nasr" Heritage is considered a system of cultural and intellectual values and principles that embody and distinguish the identity of nations. It encompasses religious, historical, intellectual, and artistic aspects. This study examines the impact of positive cultural heritage on the development of cultural awareness and its role in shaping individual personality and forming collective identity. The research focuses on the writer Ahmed Nasr as a model who reflected, through his literary works, his interaction with his cultural and social heritage despite the challenges he faced. The study revealed that drawing inspiration from heritage contributes to enhancing cultural awareness and connecting generations with their historical roots, which positively affects social cohesion and interaction with other cultures. Through the experience of Ahmed Nasr, it becomes clear how literature can serve as a means of preserving heritage and transmitting it in a modern spirit that deepens cultural awareness.